2021
DOI: 10.1039/d0na00408a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in 3D printing of nanocellulose: structure, preparation, and application prospects

Abstract: Emerging cellulose nanomaterials extracted from agricultural biomasses have recently received extensive attention due to diminishing fossil resources, with optimistic 3D printing applications in biomedical, electronics, and environmental fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 275 publications
(377 reference statements)
0
37
0
3
Order By: Relevance
“…Several processing methods have been used to produce CNC and CNF from cellulose sources, usually agricultural wastes, by exposing the basic building blocks of cellulose [ 20 ]. These methods can be summarized into two: (i) pretreatment or purification of the agricultural biomass for fractionation and (ii) treatment with the isolation of nanocellulose from purified cellulose [ 25 ]. The plant cell wall contains lignin and hemicellulose, which serve as a protective coating around the cellulose fibers, and this enables the cell wall to maintain its structured form.…”
Section: Nanocellulose: Preparation Treatment Functionality and 3d Printabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Several processing methods have been used to produce CNC and CNF from cellulose sources, usually agricultural wastes, by exposing the basic building blocks of cellulose [ 20 ]. These methods can be summarized into two: (i) pretreatment or purification of the agricultural biomass for fractionation and (ii) treatment with the isolation of nanocellulose from purified cellulose [ 25 ]. The plant cell wall contains lignin and hemicellulose, which serve as a protective coating around the cellulose fibers, and this enables the cell wall to maintain its structured form.…”
Section: Nanocellulose: Preparation Treatment Functionality and 3d Printabilitymentioning
confidence: 99%
“…Following the isolation of the nanosized cellulose particles from the pretreated fiber, a sequential chemical, enzymatic, or mechanical treatment is applied. The selection of suitable nanocellulose isolation methods depends primarily on the desired degree of crystallinity and the type of nanocellulose (CNF or CNC) of interest [ 25 ]. Fan B. et al reported the preparation of nanocellulose from the bamboo leaf that was initially pretreated by grinding, sieving, dispersion in water, ultrasonication, oven-drying, functionalization, and then subjected to further mechanical ultrasonication treatment [ 32 ].…”
Section: Nanocellulose: Preparation Treatment Functionality and 3d Printabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mesoscale architectures with programmable anisotropy and dynamic properties are created by the local control of the fibrils' orientation. The structuring of NC induced by 3D alignment, [72] the different methods of 3D printing that could be applied to NC and its composites, [73] and the challenging perspective in application [74] in particular in the medical field [75] have been recently reviewed. Among the most promising approaches for the deposition of oriented NCs is the direct ink writing, which is an extrusion-based, 3D printing combining high versatility with simplicity of operation.…”
Section: Overview Of the Deposition Techniquesmentioning
confidence: 99%
“…13 It is well established that the electrochemical properties of such electrode materials can be tuned and improved by integrating faradaic materials such as metal oxides or conducting polymers into the nanocellulose and nanocellulose-derived carbon matrices. 14 Recently, papers and fabrics made of nanocellulose [15][16][17] were reported as potential exible substrates for the deposition of electroactive materials. 18 Charge is stored electrostatically in these types of electrodes, where low internal resistances are required to facilitate rapid electron and ion transport.…”
Section: Introductionmentioning
confidence: 99%